Safety and Feasibility of Intra-Arterial Nicardipine for the Treatment of Subarachnoid Hemorrhage-Associated Vasospasm: Initial Clinical Experience with High-Dose Infusions - Tejada, J.G.; Taylor, R.A.; Ugurel, M.S.; Hayakawa, M.; Lee, S.K.; Chaloupka, J.C. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: Delayed cerebral ischemia from vasospasm is a major complication after aneurysmal subarachnoid hemorrhage (SAH), but complications and/or low efficacy are associated with current therapy. We report our initial experience with intra-arterial use of a calcium channel blocker, nicardipine.MATERIALS AND METHODS: A retrospective review of a consecutive series of patients with clinical and angiographic vasospasm treated with intra-arterial nicardipine was performed. Standard criteria for definition of significant, intractable vasospasm after aneurysmal SAH were used. After catheter angiographic confirmation of vasospasm, arteries showing severe narrowing were targeted for superselective catheterization. Nicardipine was infused at a high dose rate (0.415–0.81 mg/min). Contrast injections were performed at 2–5-mg intervals to assess effective response (a 60% increase in arterial diameter of the most severely decreased in caliber vessel compared with the very first angiographic run).RESULTS: Eleven consecutive patients underwent a total of 20 procedures; most had SAH with high Hunt and Hess grades (III or IV). All had depressed level of consciousness; others had paresis (7/20, 35%), aphasia (1/20, 5%), and facial nerve palsy (1/20, 5%). Between 10 and 40 mg of nicardipine was used. A 60% increase in diameter of the main affected artery compared with the initial diameter measured in the initial angiographic run was achieved in all procedures. Clinical improvement (resolved focal symptoms or increased Glasgow Coma Score) occurred in 10 of 11 patients (91%). One patient died from complications of the initial hemorrhage. No complications occurred after 16 of 20 procedures (80%); minor complications without sequelae occurred after the remaining procedures. Follow-up of at least 2 months in 10 survivors revealed minor or no deficits in most patients with a Glasgow Outcome Score of 1 or 2 in 9 of 10 patients (90%).CONCLUSION: In this small series, high-dose intra-arterial nicardipine infusion to treat SAH-associated vasospasm seems to be safe and effective.